Deterrence by risk of detection? An inquiry into how elite athletes perceive the deterrent effect of the doping testing regime in their sport. (4th March 2017) - Overbye, Marie
Abstract: Aims : A central paradigm of global anti-doping policy is detection-based deterrence, i.e. the risk of testing and exclusion from sport are effective doping deterrents. This paper investigates how elite athletes perceive the deterrent effect of the testing strategy in their sport and explores whether and how specific factors such as the frequency of testing influence athletes' perceptions of testing as a deterrent. Methods : 645 Danish elite athletes completed a web-based questionnaire about their perceptions of testing efforts in their sport. Findings : 75% of the athletes considered the likelihood that a test would prove positive to be a deterrent. By contrast, only 40% found the risk of being selected for testing to be a deterrent. Athletes tested frequently and athletes from doping-risk sports were more likely to perceive testing as a deterrent. In total, 24% regarded neither the likelihood of testing nor detection as deterrents. 8% did not consider the likelihood of testing and detection nor the ban from sport as deterrents. Conclusions : Testing programmes – as a strategy to detect and deter doping – are no great deterrent for many athletes. The results highlight the limitations of detection-based deterrence and emphasise a need to give higher priority to additional prevention-orientated strategies. Recommondations are outlined.